Synthesis and Biological Properties of Ketoprofen Glucopyranoside Conjugates - K. SAHU, JAGDISH; BANERJEE, LOPAMUDRA (Asian Journal of Chemistry, 2010)
Glucopyranoside conjugates of ketoprofen have been synthesized and evaluated for antiinflammatory, analgesic and ulcerogenic activities. The results designate significant augmentation in analgesic and antiinflammatory activity and diminution in gastrointestinal toxicity.